The Acceptance Model of Halal Food Products Toward Indonesian non-Muslim Customers - Baehaqi, Muhammad; Rizana, Dani; Cahyono, Ragil Setyo (IKONOMIKA, 2022)
The purpose of this study was to determine the model of acceptance of halal food products among non-Muslims in Indonesia. The proposed acceptance model is built through the collaboration of various combinations of theories such as Action Reaction Theory (TRA), Planned Behavior Theory (TPB), and Triandis Model (Triandm). This combination produces a new construct of acceptance model through the variables of inner perspective, the credibility of the halal logo, and habits as latent variables, while the acculturation variable as a mediating variable.The research was conducted in Indonesia with 317 respondents taken using non-probability sampling technique through purposive sampling method in 24 provinces. The proposed model shows positive and significant results. The inner perspective as a construct that represents a combination of norm variables in TRA and TPB, as well as social variables in TRIANDM shows positive results on acceptance and also positive on acculturation. Likewise with the credibility of the halal logo and the habit of convincing with a positive relationship to acculturation, but in relation to acceptance, the habit shows an insignificant value. Acculturation is a very decisive variable in this study, besides having a significant influence on customer acceptance it is also a mediation for other constructs.The findings in this study indicate the alignment of the model in the propositions tested. The research results also prove the theoretical alignment of several combinations of theories. Finally, because it was not found in previous research in a similar study, this research can be a pioneer in formulating an appropriate model of acceptance for non-Muslim consumers in Indonesia towards halal food.